Eine neue Stenus-Art aus dem Karpathengebiet (Coleoptera, Staphylinidae). - Puthz, Volker (Contributions to Entomology = Beiträge zur Entomologie, 1991)
Stenus (Parastenus) biharmontis sp. n. is described from the Carpathian montains (Bihar, Romania) and compared with S. trisulcatus L. Benick, which is recorded for the first time from the Muntii Tarcului. Nomenclatural Acts biharmontis Puthz, 1991 (Stenus (Parastenus)), spec. n.